Planificación en la comunicación como una estrategia para mejorar los procesos de información en la jefatura de comunicación social del gobierno autónomo descentralizado municipal Francisco de Orellana. Período octubre 2012-junio de 2013 - Granda Granda, Jorge (2014)
The research work was carried out in the Goverment Decentralized Auto-nomous Francisco de Orellana, whose objective, is to improve de commu-nication processes in the leadership of social communication of the same, through a planning of internal communication which enable them to developed and meet in a manner consistent and efficient communication of the municipality as long as it does not affect the institutional interests. It is also developing a field research which we were able to determine the strengths, opportunities, weakness and threats, to the system of commu-nication used by the Municipality of Orellana, having determined the con-clusions and recommendations of the case. And based on this research and accomplishing the goals formulated. It is a proposal of INTERNAL COMMUNICATION, whose objective is to aim to strengthen to the munici-pality of Orellanain the framework of communication compared to the processes of continuous changes that confront in the social environment and thus in political management and functional of the same. It should be emphasized that it is implementing a suitable mean for the communication in this municipality, which will require substantial changes in the reward that not particular interests but rather the institution for better information. It is fundamental importance to focus the importance of contribution to the first authority and his team necessary collaboration, the works that highlight the primary needs of the institution. The communication plan proposed focuses to inform the citizenry efficiently by appropriate mean and the best way so the municipality performs plans, controls and running on the benefits of himself and all. A good research for the communication of the municipalities that want to communicate more and better to their citizens must be truthful, honest and realistic, using professional ethics for internal those interested in communication and management